Control de inventario del Comercial Lucy Plast de la ciudad de Babahoyo - Díaz Bustamante, Nadine Silene (2021)
The present case study called Inventory Control and Profits of the Lucy Plast Commercial in the city of Babahoyo, aims to analyze the existing shortcomings in the premises due to the use of an inadequate method for handling incoming and outgoing merchandise due to the Increased demand with the arrival of COVID-19 in the country, which generated a high growth of businesses and enterprises by citizens who use the resources and materials sold by the entity. For the development of the current document, a descriptive-bibliographic research methodology is implemented, since, with the help of the techniques to be used for data collection such as the survey and the interview, each of the particularities will be analyzed. found according to the inventory control of the Lucy Plast company, validating the pertinent information with existing concepts based on the main topic using the deductive method, to validate what is described below.